PERSEPSI TERHADAP MAKANAN TRADISIONAL JAWA TIMUR: STUDI AWAL TERHADAP MAHASISWA PERGURUAN TINGGI SWASTA DI SURABAYA - Priskila Adiasih; Ritzky K.M.R. Brahmana (KINERJA, 2015)
Traditional food seems to not have a big appeal for students and that it is not as good as modern food. Interestingly, the students can not define which one is the traditional food. The lack of the knowledge of the traditional food makes them confused since in their own household they are never given the information about it. Although the traditional food is being offered at a unique restaurant with a good atmosphere and good visual, they do not think it is enough for them to choose the traditional food over modern food.Keywords: indonesia, traditional food, consumer perceptions